PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN ANIMASI SWISHMAX TERHADAP HASIL PRAKTEK MEMBUAT PUFF PASTRY SMK IMELDA MEDAN - Adikahriani Adikahriani; Nike Lora Sinulingga (Universitas Negeri Medan, 2020)
ABSTRACT This study aims to: (1) To determine the results of student practice using Swishmax animation learning media in making puff pastry. (2) To determine the results of student practice using image learning media in making puff pastry. (3) To determine the effect of Swishmax animation learning media on the making of puff pastry. The results of the t test analysis showed that there was a significant effect on the results of the practice of puff pastry using the Swishmax animation media with the tcount t table (14.60 1.6701) with a significant level of 5%. This means that the swishmax animation media can influence the results of the puff pastry practice of the Imelda Tourism Vocational School students in Medan. Based on the data obtained, it can be concluded that the Swishmax animation media has an effect on the results of the puff pastry practice of the Imelda Tourism Vocational School students in Medan.Keywords: Swishmax Animation Media, Puff Pastry Practice Results ABSTRAKPenelitian ini bertujuan untuk : (1) Untuk mengetahui hasil praktek siswa yang menggunakan media pembelajaran animasi swishmax pada pembuatan puff pastry. (2) Untuk mengetahui hasil praktek siswa yang menggunakan media pembelajaran gambar pada pembuatan puff pastry. (3) Untuk mengetahui pengaruh media pembelajaran animasi swishmax terhadap pembuatan puff pastry. Hasil analisis uji t menunjukan bahwa terdapat pengaruh yang signifikan pada hasil praktek puff pastry mengunakan media animasi swishmax dengan nilai thitung 12>